An alternative method in triaxial tests to obtain cross-anisotropic elastic parameters. Issue 3 (9th September 2020) - Nishimura, Satoshi; Magalona, Fernnie
Abstract : A new, alternative approach in a triaxial set-up to fully determine small-strain cross-anisotropic elastic parameters is proposed, which requires neither radial strain sensors nor a radial loading process. This was made possible by additionally measuring pore water pressure responses during undrained axial loading, and inputting them into theoretical expressions derived based on cross-anisotropic elasticity theory. Although the method is intended for saturated soils, slight undersaturation in the system is accounted for by incorporating the pore water pressure coefficient B into the parameter deduction process. Being free from the cumbersome radial sensors and ultra-precise cell pressure controlling devices/operations, the proposed method is applicable even in less specialised laboratories. Four different deduction routes of elastic parameters were applied to results from tests on two reconstituted fine-grained soils. The horizontal Young's modulus obtained with the newly proposed method is consistent not only with those based on radial measurements, but also with those directly measured by axial loading on horizontally cut specimens. A challenge is still open for precisely determining Poisson's ratios, which exhibited only partial matching between different measurement methods. Overall, however, the proposed method is consistent with those adopting full local instrumentation.